(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
Motivation plays a very important role in human life. Motivation is a direct assistant of a modern leader in management. In order to be a good leader, a leader needs to know how to motivate employees in which situations. The task of modern labor motivation is to create conditions for the most effective use of personnel potential. The results of the study of motivation models allow to determine what motivates a person to work. One of the main tasks of management is to determine the motives of each employee’s activity and coordinate these motives with the company’s goals.